Assessment of genetically modified soybean MON 87701 × MON 89788 for renewal authorisation under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐RX‐022). (19th December 2022) - ,; Mullins, Ewen; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Naegeli, Hanspeter; Nogué, Fabien; et al.
Abstract: Following the submission of application EFSA‐GMO‐RX‐022 under Regulation (EC) No 1829/2003 from Bayer CropScience LP, the Panel on Genetically Modified Organisms of the European Food Safety Authority was asked to deliver a scientific risk assessment on the data submitted in the context of the renewal of authorisation application for the insect‐resistant and herbicide‐tolerant genetically modified soybean MON 87701 × MON 89788, for food and feed uses, excluding cultivation within the European Union. The data received in the context of this renewal application contained post‐market environmental monitoring reports, a systematic search and evaluation of literature, updated bioinformatic analyses, and additional documents or studies performed by or on behalf of the applicant. The GMO Panel assessed these data for possible new hazards, modified exposure or new scientific uncertainties identified during the authorisation period and not previously assessed in the context of the original application. Under the assumption that the DNA sequences of the events in soybean MON 87701 × MON 89788 considered for renewal are identical to the sequences of the originally assessed event, the GMO Panel concludes that there is no evidence in renewal application EFSA‐GMO‐RX‐022 for new hazards, modified exposure or scientific uncertainties that would change the conclusions of the original risk assessment on soybean MON 87701 × MON 89788.